Quiet eye and motor performance: The longer the better? - Klostermann, A.; Kredel, R.; Hossner, E. J. (Journal of Sport & Exercise Psychology, 2018)
The quiet-eye (QE) phenomenon has been found to predict subsequent motor performance. However, it remains unclear whether this effect also holds for considerably extended QE durations. Therefore, in 2 ball-throwing studies, QE durations of 400-3,200 ms were experimentally induced. Inferior performance was found in short QE-duration conditions; however, there was no difference between the long QE-duration conditions. Extrapolations beyond the observed QE values showed performance gains up to 2,000 ms and a shallow interval of optimality at a QE duration of about 3,000 ms. These results, together with the fact that the intended absolute QE durations were not achieved, point toward an inhibition explanation of the QE. Thus, the initial performance gain is interpreted as shielding of the movement parameterization against suboptimal alternatives, whereas the performance loss due to very long QE durations is ascribed to mutually balancing the processes of shielding and environmental monitoring.